2021
DOI: 10.1038/s41467-021-23069-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-lasting renewable antibacterial porous polymeric coatings enable titanium biomaterials to prevent and treat peri-implant infection

Abstract: Peri-implant infection is one of the biggest threats to the success of dental implant. Existing coatings on titanium surfaces exhibit rapid decrease in antibacterial efficacy, which is difficult to promisingly prevent peri-implant infection. Herein, we report an N-halamine polymeric coating on titanium surface that simultaneously has long-lasting renewable antibacterial efficacy with good stability and biocompatibility. Our coating is powerfully biocidal against both main pathogenic bacteria of peri-implant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 162 publications
(101 citation statements)
references
References 55 publications
1
100
0
Order By: Relevance
“…By incorporating the N -halamine moiety, Wu et al recently reported that a porous polymeric coating on titanium surfaces can function as long-lasting and renewable antibacterial biomaterials to prevent and treat peri-implant infections. 279 Peri-implant infection is one of the biggest reasons that lead to dental implant failure. However, the existing antibacterial coating on titanium usually showed a rapid decrease in antibacterial efficiency.…”
Section: Biomedical Applications Of Popsmentioning
confidence: 99%
“…By incorporating the N -halamine moiety, Wu et al recently reported that a porous polymeric coating on titanium surfaces can function as long-lasting and renewable antibacterial biomaterials to prevent and treat peri-implant infections. 279 Peri-implant infection is one of the biggest reasons that lead to dental implant failure. However, the existing antibacterial coating on titanium usually showed a rapid decrease in antibacterial efficiency.…”
Section: Biomedical Applications Of Popsmentioning
confidence: 99%
“…[3,4] Therefore, the development of smart and robust antibacterial coatings has attracted great attentions during the past decade, owing to their efficient antibacterial activities and facile surface engineering process without damaging the substrates. [5] Several fabrication strategies toward functional antimicrobial coatings have been widely developed so far, including Langmuir-Blodgett (LB) deposition, Langmuir-Schaefer (LS) deposition, and Layer-by-Layer (LBL) assembly. [6,7] In addition, several kinds of dry methods have also widely used for the preparation of antimicrobial coatings, such as radical-rich plasma activated coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Antibacterial analysis for this functionalised surface was studied against S. aureus and Pseudomonas gingivalis. The results suggest that Ti-PAA-NCl is capable of inhibiting 96% of S. aureus and 91% of P. gingivalis [120]. In another investigation, silver nanoparticle AgNPs were incorporated in CaP-coated zirconia ceramics.…”
Section: Surface Engineering Strategiesmentioning
confidence: 93%